The impact of emotional solidarity on festivals visitors’ satisfaction. Does the festival authenticity matter? - Ayad, Tamer Hamdy; Hasanein, Ahmed M.; Ghaly, Meril (Edelweiss Applied Science and Technology, 2024)
Festivals offer more than just entertainment, it considered a powerful platform for emotional connection and cultural exchange. This study explores the impact of emotional solidarity on festival visitors’ satisfaction. It also examines the moderating role of festival authenticity in the relationship between emotional solidarity and festival visitors’ satisfaction. Quantitative approach using 456 self-administered questionnaire directed to festival visitors in Egypt and Saudi Arabia. The findings reveal that all three dimensions of emotional solidarity welcoming nature, emotional closeness, and sympathetic understanding have a direct and significant positive impact on visitors’ satisfaction. Furthermore, festival authenticity plays as a moderator between emotional solidarity dimensions and festival visitors’ satisfaction. The study discusses both theoretical and practical implications of these findings for festival organizers and tourism researchers.